A young woman with chest pain. Issue 6 (1st December 2000) - Missouris, C G; Ring, A; Ward, D
Abstract : A case of a previously fit young woman admitted with chest pain, who was found at coronary angiography to have dissection of the left main stem which extended to the left anterior descending and circumflex coronary arteries, is presented. Emergency coronary artery bypass grafting was performed (vein grafts to the left anterior descending, the diagonal, and circumflex arteries). The patient made an uneventful recovery, and three years after initial presentation she remains free of cardiac symptoms.